Natural product sennoside B disrupts liquid-liquid phase separation of SARS-CoV-2 nucleocapsid protein by inhibiting its RNA-binding activity - Da-Wei Zhang; Xiao-Shuang Xu; Liangxu Xie; Lei Xu; Zhiguo Fu; Yimin Li; Xiaojun Xu (Journal of Enzyme Inhibition and Medicinal Chemistry)
The nucleocapsid protein (NP) of SARS-CoV-2, an RNA-binding protein, is capable of undergoing liquid-liquid phase separation (LLPS) during viral infection, which plays a crucial role in virus assembly, replication, and immune regulation. In this study, we developed a homogeneous time-resolved fluorescence (HTRF) method for identifying inhibitors of the SARS-CoV-2 NP-RNA interaction. Using this HTRF-based approach, we identified two natural products, sennoside A and sennoside B, as effective blockers of this interaction. Bio-layer interferometry assays confirmed that both sennosides directly bind to the NP, with binding sites located within the C-terminal domain. Additionally, fluorescence recovery after photobleaching (FRAP) experiments revealed that sennoside B significantly inhibited RNA-induced LLPS of the NP, while sennoside A displayed comparatively weaker activity. Thus, the developed HTRF-based assay is a valuable tool for identifying novel compounds that disrupt the RNA-binding activity and LLPS of the SARS-CoV-2 NP. Our findings may facilitate the development of antiviral drugs targeting SARS-CoV-2 NP.